Endometrial stromal sarcoma - Puliyath Geetha; Nair Rajasekharan; Singh Swetha (Indian Journal of Medical and Paediatric Oncology)
Endometrial stromal sarcoma (ESS) is a rare malignant tumor of the endometrium, occurring in the age group of 40-50 years. This is a case of low-grade ESS presenting as rapid enlargement of a fibroid uterus. Because of her secondary infertility, she was planned for myomectomy. However, due to the high degree of suspicion of a sarcomatous change in the fibroid, in view of rapid enlargement of uterus within the last 4 months, we planned for a preoperative endometrial aspiration. It showed low-grade ESS, which was later confirmed by histopathology examination of total hysterectomy specimen. As surgery was the main treatment for ESS, because of the proper preoperative diagnosis, we could plan the treatment accordingly. Despite the rarity of the tumor, one has to consider the possibility of ESS in cases with presentation of rapid enlargement of a fibroid uterus.